2005
DOI: 10.1001/archpsyc.62.11.1205
|View full text |Cite
|
Sign up to set email alerts
|

Association of DISC1/TRAX Haplotypes With Schizophrenia, Reduced Prefrontal Gray Matter, and Impaired Short- and Long-term Memory

Abstract: Specific alleles of the DISC1 and TRAX genes on 1q42 appear to contribute to genetic risk for schizophrenia through disruptive effects on the structure and function of the prefrontal cortex, medial temporal lobe, and other brain regions. These effects are consistent with their production of proteins that play roles in neuritic outgrowth, neuronal migration, synaptogenesis, and glutamatergic neurotransmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
224
4
4

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(242 citation statements)
references
References 61 publications
9
224
4
4
Order By: Relevance
“…2 A number of studies have since reported evidence of linkage or association between the DISC1 locus and impaired cognitive function in both schizophrenic and normal individuals (Table 1b, Figure 1a). 22,25,[35][36][37][38][39][40] These deficits are consistent with dysfunction in the dorsolateral prefrontal cortex (PFC) and the hippocampus.…”
Section: Disc1 Variation and Cognitive Abilitiesmentioning
confidence: 76%
See 2 more Smart Citations
“…2 A number of studies have since reported evidence of linkage or association between the DISC1 locus and impaired cognitive function in both schizophrenic and normal individuals (Table 1b, Figure 1a). 22,25,[35][36][37][38][39][40] These deficits are consistent with dysfunction in the dorsolateral prefrontal cortex (PFC) and the hippocampus.…”
Section: Disc1 Variation and Cognitive Abilitiesmentioning
confidence: 76%
“…25 A similar trend towards decreased hippocampal volume has also been reported in the Finnish population for the DISC1-associated haplotype HEP1. 36 In contrast to these studies, Hashimoto et al 27 did not find decreases in hippocampal volume associated with the Ser704Cys polymorphism in their Japanese control sample; however, they did report decreases in the grey matter of the cingulate cortex, cingulate gyrus and the posterior gyrus, and abnormalities in prefrontal white matter, in carriers of the Cys704 allele. Therefore, while this study supports the idea that the Ser704Cys polymorphism is associated with reductions in brain tissue volume, the regions of volume reduction differ and the allele associated with the reductions differs also.…”
Section: Disc1 Variation and Cognitive Abilitiesmentioning
confidence: 81%
See 1 more Smart Citation
“…The translocation disrupts a gene termed disrupted-in-schizophrenia 1 (DISC1) on chromosome 1. 5,7,9 Linkage and association at the DISC1 locus have been demonstrated for psychiatric illness in several populations, [10][11][12][13][14][15][16][17] suggesting wider relevance of DISC1.…”
Section: Introductionmentioning
confidence: 99%
“…The potential contributions of DISC1/2 and a nearby TRAX gene to the pathogenesis of schizophrenia were subsequently supported by a number of, but not all, genetic association studies in the general population, including those with different ethnic genetic backgrounds. 2 However, the odds ratios are modest for DISC1 as a susceptibility gene and functional mutations have not been identified. In contrast, the t(1; 11) translocation in the Scottish family appears to be the causal genetic lesion with 70% penetrance for major mental illness.…”
mentioning
confidence: 99%